The application of SSRs characterized for grape (Vitis vinifera) to conservation studies in Vitaceae - Arnold, Claire; Rossetto, Maurizio; McNally, Jody; Robert J. Henry, Robert J. (My University, 2020)
The use of microsatellite loci developed from a single plant species across a number of related taxa is becoming increasingly widespread. This approach can provide highly informative markers even for species for which microsatellites have not been characterized. As a number of expressed sequence tag (EST)-derived and enrichment-derived microsatellites are available for grape (Vitis vinifera), this study set out to assess transferability of nine such loci across 25 species from five different Vitaceae genera. Intergeneric transfer success in Vitaceae was high (51.1%) and EST-derived loci performed better than enrichment-derived loci. Six loci were further tested across two Australian native species, Cissus hypoglauca and C. sterculiifolia, in order to assess the conservation of microsatellite repeats and their flanking sequences. Polymorphism of these selected loci was successfully tested for each species across a small, isolated rain forest population from northern New South Wales (Australia). Results from this preliminary investigation suggest that it is possible to use grape-derived simple sequence repeats (SSR) loci for population studies on Vitaceae. As Vitaceae are an important component of rain forest flora, the availability of such highly informative loci will be beneficial to future studies aimed at determining the genetic consequences of rain forest fragmentation.
Keywords: Cissus; microsatellites; SSR loci transfer; Vitis; Vitaceae